2015
DOI: 10.1016/j.jiph.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Community- versus nosocomial-acquired severe sepsis and septic shock in patients admitted to a tertiary intensive care in Saudi Arabia, etiology and outcome

Abstract: Both community and hospital-acquired infections carry high mortality. Hospital-acquired severe sepsis is frequent in medical wards and ICUs, and measures to further evaluate risk factors are prudent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…The majority of SS cases were hospital-acquired, corroborating with the results of Baharoon et al on the epidemiology of sepsis in an tertiary ICU of Saudi Arabia. 22 Similarly to Baharoon et al in Saudi Arabia, 22 the main comorbidities were hypertension followed by diabetes. Also, like previous reports, 11,12,19,21 the most common sites of infection responsible for SS were the lungs followed by the abdomen.…”
Section: Discussionmentioning
confidence: 81%
“…The majority of SS cases were hospital-acquired, corroborating with the results of Baharoon et al on the epidemiology of sepsis in an tertiary ICU of Saudi Arabia. 22 Similarly to Baharoon et al in Saudi Arabia, 22 the main comorbidities were hypertension followed by diabetes. Also, like previous reports, 11,12,19,21 the most common sites of infection responsible for SS were the lungs followed by the abdomen.…”
Section: Discussionmentioning
confidence: 81%
“…Sepsis is a life-threatening disease that requires early recognition and immediate management. A local study conducted at the National Guard Hospital in Riyadh, Saudi Arabia, showed that the mortality rates for sepsis and septic shock were higher than the reported global mortality rates approaching 60% 1 . Internationally, the incidence and severity of sepsis reveal a rising pattern 2 , 3 .…”
Section: Introductionmentioning
confidence: 95%
“…[3,29,30] In the present work, blood cultures were positive in 22.7% of septic patients, with slight predominance of Gram-positives. In general, the positivity of blood cultures can vary from 12.5% to no more than 40 % even in cases with septic shock [31,32,33,34]. There are many explanations why the yield of blood cultures in septic patients is so low.…”
Section: Discussionmentioning
confidence: 99%